DETERMINANT OF CUSTOMER LOYALTY FOR BANK SYARIAH INDONESIA AFTER M&A ACTIVITY BASED ON CONFIRMATORY FACTOR ANALYSIS - Mardianto, M. Fariz Fadillah; Cahyono, Eko Fajar; Previan, Anggara Teguh; Fitrianingsih, Eka Rani; Fauzan, Muhammad Hafid (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2023)
Introduction: The government of Indonesia consolidated three state-owned Islamic banks to become Bank Syariah Indonesia. Customer loyalty is affected by merger operations. The goal of this study was to look at how operational integration variables, information technology integration, bank location, service quality, bank human resource quality, and product quality affected customer loyalty at BSI's predecessor banks (Bank Syariah Mandiri, BNI Syariah and BRI Syariah). Methods: Primary data was collected using a questionnaire tool. Confirmatory Factor Analysis was employed as the analytical method. Results: Consumer loyalty to BSI post the merger is influenced by a number of variable aspects, according to the study's findings. All operational integration variables, IT integration, bank location, service quality, HR quality, and product quality have a major effect on BSI customer loyalty, but the operational integration variables, IT integration, and product quality have the most significance. Conclusion and suggestion: BSI perform operational integration, fast and good IT integration, and has better product quality than before the merger, the most influencing factor for customers to be loyal to BSI is when BSI performs operational integration, fast and good IT integration, and has better product quality than before the merger.